Booties in Al-Rashidi age(11-41 AH.)(601/661 AH): Historical study - Al –Azergawi, Kassim Jodah Adday (Al-Adab Journal, 2020)
This study cars with booties studies in Al-Rashidi age limited of period (11-41 AH)(601/632/661 AH), as for the place covers Morocco and the Levant countries, the booties subject obtains significant importance in Islamic history, being nerve of economic life in Islam threshold, thus this research cares with studying it considering the historical aspect with illustrating its kind and size in Al-Rashidi age has witnessed persistence movement of the Islamic conquests. Represented a complete to what messenger ( peace be upon him) started, it is obvious to be accompanied that the conquers obtained the enemy booties, the Muslims offered to cities residences to convert Islam or tribute, the one who refuse to be fight and to confiscate his monies It is worth mentioned that the most effective period, the Muslims obtained many booties was during Omar bin Al-Khatab succession, especial in conquest of Iraq. Andrich Persia, Syria( Al-Sham) country and its extensions, in Egypt.. Cyprus and morocco, importance of booties like Iraq front.